2013
DOI: 10.1152/ajprenal.00409.2012
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Na-glucose transporter SGLT2 attenuates hyperglycemia and glomerular hyperfiltration but not kidney growth or injury in diabetes mellitus

Abstract: The Na-glucose cotransporter SGLT2 mediates high-capacity glucose uptake in the early proximal tubule and SGLT2 inhibitors are developed as new antidiabetic drugs. We used gene-targeted Sglt2 knockout (Sglt2(-/-)) mice to elucidate the contribution of SGLT2 to blood glucose control, glomerular hyperfiltration, kidney growth, and markers of renal growth and injury at 5 wk and 4.5 mo after induction of low-dose streptozotocin (STZ) diabetes. The absence of SGLT2 did not affect renal mRNA expression of glucose tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
311
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(365 citation statements)
references
References 47 publications
33
311
1
4
Order By: Relevance
“…In a short-term study, Malatiali et al (43) observed that the nonspecific SGLT inhibitor phlorizin reduced the increase in kidney size and the glomerular hyperfiltration in streptozotocin-induced diabetic Fisher rats. Different results have been observed in streptozotocin-induced diabetic SGLT2 knockout mice, where there was a reduction in hyperfiltration but not in renal hypertrophy and in markers of inflammation or fibrosis compared with the wild-type diabetic mice (34). As outlined above, data in animal models often differ depending upon the model used.…”
Section: Sglt2 Inhibitors: Experimental Datamentioning
confidence: 95%
See 1 more Smart Citation
“…In a short-term study, Malatiali et al (43) observed that the nonspecific SGLT inhibitor phlorizin reduced the increase in kidney size and the glomerular hyperfiltration in streptozotocin-induced diabetic Fisher rats. Different results have been observed in streptozotocin-induced diabetic SGLT2 knockout mice, where there was a reduction in hyperfiltration but not in renal hypertrophy and in markers of inflammation or fibrosis compared with the wild-type diabetic mice (34). As outlined above, data in animal models often differ depending upon the model used.…”
Section: Sglt2 Inhibitors: Experimental Datamentioning
confidence: 95%
“…Thus, SGLT2 inhibition should result in an increased delivery of sodium to the macula densa, a consequent increase in adenosine release, resulting in vasoconstriction of the afferent arteriole leading to a reduction in renal plasma flow and GFR. Accordingly, in SGLT2 knockout mice, the induction of diabetes was associated with less hyperfiltration compared with wildtype diabetic mice (34). Micropuncture studies in rats with streptozotocininduced diabetes treated with SGLT2 inhibitors demonstrated reductions in proximal sodium reabsorption and in single nephron GFR (35).…”
Section: Sglt2 Inhibitors and Glomerular Hyperfiltrationmentioning
confidence: 99%
“…A recent emphasis is placed on the role of the tubulointerstitium in kidney disease, and its contribution to both initial events perturbing kidney function, but also in sustaining renal injury. [10][11][12] A tubular hypothesis whereby PT growth promotes PT hyper-reabsorption, which in turn contributes to hyperfiltration and hypertension, leading to further renal injury, is now given significant recognition in the literature (reviewed in Vallon and Thomson 12 ). Transforming growth factor beta (TGFβ) is a key regulator of PT changes, promoting and maintaining alterations in growth and fibrotic responses.…”
mentioning
confidence: 99%
“…Increased SGLT2 expression has previously been identified in PTCs isolated from the urine in T2D patients (Rahmoune et al 2005). However, mice that have the expression of Sglt2 ablated in the PTCs are not protected against the development or progression of kidney injury (Vallon et al 2013). Whether increased expression of SGLT2 correlates with an increased risk of the development of DN is yet to be determined.…”
Section: Mechanisms Culminating a Stressed Diabetic Ptc Ermentioning
confidence: 99%